Dates Palm Farming in Malaysia: Current Challenges and Future Baraqah - Aimi Fadzirul Kamarubahrin; Siti Nurazira Mohd Daud; Muhammad Iqmal Hisham Kamaruddin; Asmaddy Haris; Zurina Kefeli@ Zulkefli; Nursilah Ahmad; Syadiyah Abdul Shukor; Nurul Aini Muhamed (USIM Press, 2024)
Contemporary Issues: Islam & Science